2021
DOI: 10.3171/2020.6.spine20898
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the unique characteristics associated with surgical treatment of dystrophic lumbar scoliosis secondary to neurofibromatosis type 1: a single-center experience of more than 10 years

Abstract: OBJECTIVEDystrophic lumbar scoliosis secondary to neurofibromatosis type 1 (DLS-NF1) may present an atypical, unique curve pattern associated with a high incidence of coronal imbalance and regional kyphosis. Early surgical intervention is complicated and risky but necessary. The present study aimed to assess the unique characteristics associated with the surgical treatment of DLS-NF1.METHODSThirty-nine consecutive patients with DLS-NF1 treated surgically at a mean age of 14.4 ± 3.9 years were retrospectively r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Screw malposition in dystrophic scoliosis cases is relatively high, at 20% to 30%. 25,28 Potential poor fixation and screw malpositioning should be considered during opera- tive planning, as this may affect the surgeon's ability to perform high-grade osteotomies and ultimately correct the deformity. 29 Nonetheless, high implant density should be the goal with hybrid constructs, as this will optimize chances of greater deformity correction and decreased loss of correction.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Screw malposition in dystrophic scoliosis cases is relatively high, at 20% to 30%. 25,28 Potential poor fixation and screw malpositioning should be considered during opera- tive planning, as this may affect the surgeon's ability to perform high-grade osteotomies and ultimately correct the deformity. 29 Nonetheless, high implant density should be the goal with hybrid constructs, as this will optimize chances of greater deformity correction and decreased loss of correction.…”
Section: Discussionmentioning
confidence: 99%
“…44 As expected, pedicle dysplasia results in high rates of malpositioned screws, with one study reporting an incidence of 30.5% (9.9% medial and 20.6% lateral) with the freehand insertion technique. 28 Navigation allows surgeons to circumvent some of the challenges, but the true problem is the lack of osseous volume to simply place a screw. Jin et al showed that navigation can decrease the misplaced screw rates, but even with navigation guidance, more than 20% of screws were still malpositioned.…”
Section: Spinal Fixation and Instrumentationmentioning
confidence: 99%
See 3 more Smart Citations